2020
DOI: 10.1101/2020.02.17.919845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of structural stability on endolysosomal degradation and T-cell reactivity of major shrimp allergen tropomyosin

Abstract: Background: Tropomyosins are highly conserved proteins, an attribute that forms the molecular basis for their IgE antibody cross-reactivity. Despite structural similarities, their allergenicity varies greatly between ingested and inhaled invertebrate sources. In this study, we investigated the relationship between the structural stability of different tropomyosins, their endolysosomal degradation patterns and T-cell reactivity. Methods:We investigated the differences between four tropomyosins -the major shrimp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…We recently showed that T-cell cross-reactivity among tropomyosins is not dependent on amino acid sequence similarity, but instead as a function of structural stability. 6 This supports our findings that tropomyosins from different invertebrate sources may produce cross-reactive antibodies, even when sharing low amino acid sequence similarity 7 Our findings suggest that primary sensitization to tropomyosin from mollusk is possible, and inverse clinical cross-reactivity may occur to crustaceans in molluskallergic individuals.…”
Section: Mollusk Allergy: Not Simply Cross-reactivity With Crustacean...supporting
confidence: 82%
“…We recently showed that T-cell cross-reactivity among tropomyosins is not dependent on amino acid sequence similarity, but instead as a function of structural stability. 6 This supports our findings that tropomyosins from different invertebrate sources may produce cross-reactive antibodies, even when sharing low amino acid sequence similarity 7 Our findings suggest that primary sensitization to tropomyosin from mollusk is possible, and inverse clinical cross-reactivity may occur to crustaceans in molluskallergic individuals.…”
Section: Mollusk Allergy: Not Simply Cross-reactivity With Crustacean...supporting
confidence: 82%
“…This is in line with the enhanced susceptibility to proteases of L89G observed in the degradome assay. We have previously found that immunodominant peptides from Bet v 1.0101 or tropomyosin ( 55 , 62 ) are quickly degraded in the degradome assay, but nevertheless are effectively presented by BMDCs in vitro , supporting the concept of “bind first, cut later.” Kim et al have shown that immunodominant epitopes are protected from further degradation by binding to MHC II, whereas epitopes sensitive to DM-mediated dissociation are destroyed by cathepsins ( 57 , 63 ). Data on the protein dynamics from aMD simulations indicated that the introduction of glycin 89 enhanced the flexibility in the alpha helix (91–96) adjacent to the epitope ( Figure 4 ) facilitating access to additional cleavage sites ( Figures 6C,D ) and/or binding to MHC II.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to resistance to extracellular digestion by gastrointestinal proteases, the resistance to endosomal degradation (i.e. digestion within the antigen‐processing and presenting cells (APC) of the immune system, such as dendritic cells) and its relationship with a protein’s capability to act as an allergen has been less studied (Foster et al, 2013; Machado et al, 2016; Soh et al, 2019; Kamath et al, 2020). To be recognised as an allergen, exogenous antigens must first be internalised into the endosome of APC and then are subjected to endosomal degradation, where they are exposed to cathepsin proteases under increasingly acidic and reducing conditions.…”
Section: Assessmentmentioning
confidence: 99%